Crashworthiness design of graded cellular materials: Experimental verification of the backward design strategy. (January 2023) - Chang, Baixue; Zheng, Zhijun; Zhang, Yuanrui; Zhang, Yongliang; Zhao, Kai; Yu, Jilin
Highlights: A two-specimen test method is developed to determine the D-R–PH material parameters. Specimens of graded cellular material are designed by using the D-R–PH backward design strategy. Additive manufacturing is employed to fabricate density-gradient ABS cellular materials. A constant impact force acting on the protected object is successfully controlled in impact tests. Experiments have verified the feasibility and reliability of the crashworthiness design strategy. Abstract: Graded cellular materials with a suitable design may improve the crashworthiness of protective structures. A backward design strategy considering the loading-rate sensitivity of cellular material has been proposed in the companion paper to guide the crashworthiness design of graded cellular material for protecting a moving object. Detailed experimental results are presented in this study to verify the feasibility and estimate the accuracy of this design strategy. A rate-dependent, rigid–plastic hardening (D-R–PH) idealization was employed to model cellular materials. A two-specimen test method was developed to determine the dynamic material parameters and their relationship with the relative density for the crashworthiness design. A power-law relationship between the dynamic material parameters and the relative density for the closed-cell foam with acrylonitrile butadiene styrene (ABS) plastic as the matrix material was obtained and employed in the crashworthiness design. Additive manufacturing was employed to fabricate the designed graded cellular specimens with ABS plastic, and the Taylor–Hopkinson pressure bar experimental technique together with high-speed photography was applied to perform impact tests. Graded ABS closed-cell foam specimens for different design conditions, e.g., the initial impact velocity, impact mass, and design target of impact force, were designed by the D-R–PH backward design strategy and prepared, and the corresponding impact tests were conducted. The impact force applied on the mass remains relatively stable and meets the crashworthiness requirement in all test cases. Therefore, the feasibility and reliability of the crashworthiness backward design strategy are verified, and this design strategy can be used to guide the crashworthiness design in engineering practice.